Structure and radio‐protective effects of sulfated Auricularia auricula polysaccharides. Issue 6 (16th September 2018) - Chen, Zhiqiu; Zhou, Xintao; Zhang, Jing; Zhang, Hua; Geng, Lin; Wang, Zhenyu; Regenstein, Joe M.
Abstract: Radiation‐protective effects of sulfated polysaccharides (SNAAP80) from Auricularia auricular were studied. Crude polysaccharides were extracted using ultrasound‐assisted water extraction. Bioactive polysaccharide fragments were screened using ethanol precipitation with an in vitro antioxidant activity test. The chlorosulfonic acid‐dimethylformamide method was used to obtain the sulfated polysaccharide. Monosaccharide composition and molecular weight were determined using GC‐MS and HPLC‐GPC, respectively. IR, UV, and SEM were used for structural characterization. The antiradiation effect of SNAAP80 was studied using a 60 Co‐γ radiation model in mice. The results showed that the SNAAP80, with a degree of substitution of 0.514, was composed of glucose and mannose. A bioactivity analysis showed that the SNAAP80 increased the organ indexes, phagocytosis index, stimulation index, and the superoxide dismutase, glutathione peroxidase, catalase, and lactate dehydrogenase activity. The SNAAP80 decreased TBARS, IL‐2, IL‐12, INF‐γ, protein carbonyls, creatinine, and blood urea nitrogen. The results suggested that SNAAP80 had an effective radiation‐protective effect. Practical applications: Auricularia auricula is a commonly cultivated commercial mushroom in East Asia; it is also called "wood ear" in China and "black fungus" in Russia. Many published studies regarding polysaccharides from A. auricula have shown their beneficial health effects for both humans and animals. A. auricula is acknowledged for its pharmaceutical effects such as inhibiting lipid peroxidation, decreasing liver damage, hypolipidemic properties and so on. Functional activity of polysaccharides is related to their solubility. The activities of polysaccharide NAAP80 from A. auricular were restricted because of its poor solubility. Therefore, it was modified by chlorosulphonic acid‐N, N dimethylformamide to obtain SNAAP80 which has a significantly higher solubility. Antiradiation effect of SNAAP80 has been studied in this paper, and its potential application in antiradiation may be relevant to space exploration, the military, daily health care, and therapeutic medications.